Analisis dan Perancangan Pengukuran Efektivitas Program Pelatihan Karyawan PT. X dengan Kirkpatrick Model - Anastasya Wibowo (Jurnal Titra, 2022)
PT. X is a tobacco industry company. In achieving the company's vision, one of PT. X mission is to support employees in improving their welfare by providing financial and entrepreneurship training programs. Several vendors organize the training. The implementation of the training program is measured based on participants' answers to the survey through a questionnaire. The questionnaire was designed based on the theory of the Kirkpatrick Model to make it easier for companies to process data and analyze the training. The questionnaire can describe participants' opinions regarding several factors that support the implementation of the training, the effects of the training on participants, the results of the training, and other information needed to develop the training program.